The Use of Conductive Rubber in Electrically Heated Handwear and Footwear. - Collyer,John C.; Clark,John R. (1974)
The feasibility of using electrically conductive rubber as a heating element for gloves was established. Tests were carried out in the DREO cold chamber using experimental conductive rubber elements over a temperature range from 0F down to -30F. Finger and hand temperatures of test subjects were substantially higher than those of subjects wearing the Canadian Forces cold weather mitten system. Footwear tests did not give any conclusive results due to higher skin temperatures being maintained throughout the test procedure.